San Agustín y la vida: Defensor de la vida y de la dignidad humana - Eguiarte Bendímez, Enrique A. (Mayéutica, 2021)
The article has as point of departure the idea that for Saint Augustine biological life is intimately linked with spiritual life; moreover, biological life itself is nothing but a metaphor of the real life. It is also presented that for Saint Augustine life is ultimately a Christological matter. The basic Augustinian anthropological idea of the human being as mendicus Dei is also developed, starting from the text of 1 Cor 4, 7, and developing the image of the human being as vilicus, as a simple administrator of God’s gifts. On the other hand, the issue of abortion is addressed according to the Augustinian ideas, to highlight that despite the fact that in the time of Saint Augustine a subtle distinction was made between a formed and an unformed embryo, according to the number of days of gestation, following the Aristotelian theories illuminated by the text of Ex 21, 22-23, according to the LXX, Saint Augustine opposes abortion in all cases, considering it a homicide, because whoever will become a person, is already so in the very womb of their mother. Three sources of human dignity according to Saint Augustine are also presented. In the first place, the fact that the human being has been created in the image and likeness of the Triune God. Second, the fact of Christ’s incarnation and redemption, presenting the Augustinian argument that the price of each man is none other than the blood of Christ. A third Augustinian argument is also presented, which is his condition as a son of God through the sacrament of baptism. It also presents the point of view of Saint Augustine on the death penalty, specifically in relation to the circumcelliones and the ep. 133 and the slave traders (mangones) and ep. 10*.